Konsistensi Janji Politik Pasangan Mulkan-Syahbudin Pasca Terpilih Menjadi Bupati Kabupaten Bangka Tahun 2018 - Romianti, Friska Dwi (Journal of Social Contemplativa, 2023)
The research entitled "Consistency of the Political Promises of the Mulkan-Syahbudin Couple After Being Elected to Become the Regent of Bangka Regency in 2018" focuses on a number of things, namely what marketing strategies the Mulkan-Syahbudin pair used and the implementation of the political promises that the Mulkan-Syahbudin pair made during political campaigns . The research method in this writing is descriptive qualitative research. The results of the study show that through the ten formulations of political marketing, there are six main formulations used to analyze this research, namely Polling, Profiling, Positioning, Product, Marketing Pull, and Marketing Push. The five formulations are political marketing formulations that are most highlighted by Mulkan-Syahbudin in their success in winning regional head elections in Bangka and related to the political promises put forward by the Mulkan-Syahbudin pair that have been well realized although there is still something to be done and renewed